Rural Demographic Problem Areas in Poland - Andrzej Jakubowski; Urszula Bronisz (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Demographic problem areas are perceived as one of the most important types of problem areas and require special research interest. Problem areas conditioned by population factor most often refer to rural areas. Presented article aims to identify and delimit rural demographic problem areas in Poland. The study covered rural areas distinguished on the basis of the classification of the European Commission DEGURBA The analysis enabled to identify depopulation areas, areas with disrupted population reproduction (ie areas of permanent natural decline), areas of permanent outflow of population, areas with impaired population structure by age and areas with disrupted population structure by sex in the group of people of marriage age (20-34 years). To indicate clusters of communes characterised by the presence of the unfavourable demographic phenomena and processes (rural demographic problem areas) the measure of local spatial autocorrelation (Anselin Local Moran's I) was applied. The application value resulting from the research may be the improvement of the effectiveness of public intervention carried out as part of the development policy.